Climate policies under dynamic international economic cycles: A heterogeneous countries DSGE model - Bowen Xiao; Xiaodan Guo; Ying Fan; Sebastian Voigt; Lianbiao Cui (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
In light of increased economic integration and global warming, addressing critical issues such as the role of multilateral climate policies and the strategic interaction of countries in climate negotiations becomes paramount. We thus established for this paper an open economy environmental dynamic stochastic general equilibrium model with heterogeneous production sectors, bilateral climate policies, asymmetric economies, and asymmetric stochastic shocks, using China and the EU as case studies in order to analyze the interaction and linking of international carbon markets under dynamic international economic cycles. This led us to some major conclusions. First, with various methods we verified that, due to deadweight loss, the efficiency of the separate carbon market is lower than that of the joint carbon market. Second, the intensity of the spillover effects depends partly on different climate policies. This means that, in terms of supply-side shocks, the EU's economy in a joint carbon market is more sensitive because its cross-border spillover effects are enhanced, while demand-side shocks have a stronger impact on the EU's economy under a separate carbon market. Third, the Ramsey policy rule revealed that both China's and the EU's emission quotas should be adjusted pro-cyclically under separate carbon markets. The cross-border spillover effects of the joint carbon market, however can change the pro-cyclical characteristics of foreign (EU's) optimal quotas.
Keywords: E32; F41; Q53; Q56; Q58; 330; International economic cycle; Carbon market; China; the European Union (EU); Dynamic Stochastic General Equilibrium (DSGE)